2014
DOI: 10.1002/2014jd022305
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale dynamics associated with clustering of extratropical cyclones affecting Western Europe

Abstract: Some recent winters in Western Europe have been characterized by the occurrence of multiple extratropical cyclones following a similar path. The occurrence of such cyclone clusters leads to large socio-economic impacts due to damaging winds, storm surges, and floods. Recent studies have statistically characterized the clustering of extratropical cyclones over the North Atlantic and Europe and hypothesized potential physical mechanisms responsible for their formation. Here we analyze 4 months characterized by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
131
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 100 publications
(159 citation statements)
references
References 76 publications
11
131
1
Order By: Relevance
“…The maintenance of these large-scale conditions is supported by two-sided Rossby wave breaking over the North Atlantic (Hanley and Caballero, 2012;Go´mara et al, 2014;Messori and Caballero, 2015). Pinto et al (2014) demonstrated for four selected stormy periods 1990, 1993, 1999 and 2007 that secondary cyclogenesis (new storms develop on the trailing fronts of previous storms, cf . Parker, 1998) further contributes to the occurrence of cyclone clusters arriving into Western Europe in rapid succession.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maintenance of these large-scale conditions is supported by two-sided Rossby wave breaking over the North Atlantic (Hanley and Caballero, 2012;Go´mara et al, 2014;Messori and Caballero, 2015). Pinto et al (2014) demonstrated for four selected stormy periods 1990, 1993, 1999 and 2007 that secondary cyclogenesis (new storms develop on the trailing fronts of previous storms, cf . Parker, 1998) further contributes to the occurrence of cyclone clusters arriving into Western Europe in rapid succession.…”
Section: Introductionmentioning
confidence: 99%
“…Such stormy winters are characterised by the frequent occurrence of cyclone families (Bjerknes and Solberg, 1922). Pinto et al (2014) recently provided evidence that the occurrence of cyclone clusters is governed by a persistent, zonally orientated and extended eddy-driven polar jet stream over the eastern North Atlantic and Western Europe, which drives the North Atlantic cyclones towards the British Isles and sometimes further into Central Europe. The maintenance of these large-scale conditions is supported by two-sided Rossby wave breaking over the North Atlantic (Hanley and Caballero, 2012;Go´mara et al, 2014;Messori and Caballero, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Variations in the UTLS jets influence influence surface weather patterns (e.g., see reviews by Lucas et al, 2014;Harnik et al, 2016) such as rainfall changes (e.g., Price et al, 1998;Raible et al, 2004;Karnauskas and Ummenhofer, 2014;Huang et al, 2015;Xie et al, 2015;Delworth and Zeng, 2014;Bai et al, 2016), destructive wind storms (e.g., Pinto et al, 2009Pinto et al, , 2014Gómara et al, 2014;Messori and Caballero, 2015), and extreme temperature events (e.g., Francis and Vavrus, 2012;Harnik et al, 2016). Moreover, transport processes that alter the extent and consequences of extratropical stratosphere-troposphere exchange (STE) are closely linked to the tropopause and jets, which are themselves sensitive to climate change and ozone depletion (e.g., Seidel and Randel, 2006;Lorenz and DeWeaver, 2007;Polvani et al, 2011;WMO, 2011;Hudson, 2012;Grise et al, 2013;Waugh et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This research raised much awareness about clustering in the natural catastrophe insurance industry that has led to major developments in windstorm catastrophe models (Khare et al 2014). The findings are also stimulating new research into mechanisms for clustering of extreme storms (e.g., Rossby wave breaking; Pinto et al, 2014). 15…”
Section: Uncertainty Quantification In Windstorm Hazard Estimationmentioning
confidence: 99%